Analisis Penggunaan Laboratorium IPA Fisika di Sekolah Menengah Pertama/Madrasah Tsanawiyah - Hurriyah, Hurriyah (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2018)
The Goal of this paper is to analyze the use of science laboratory specially physics laboratory in junior high school. The research method uses library research. The results of the study can be seen that laboratory is one of important thing to encourage interaction between student and learning object on junior high school. Laboratory and all of kind the tool is important to support learning proses in school as write as in government role at PP number 19 2005 abaut National education standard. Component of education laboratory consist of 5 component, there are laboratory’s building, facilities, tools, chemical, and organizing (Wahyukaeni, 2005: 18-21)